Effect of Asset Structure and Firm Size on Capital Structure (Case Study on Food and Beverage Companies on the Indonesian Stock Exchange) - Feni, Feni; Burhanuddin, Burhanuddin; Guasmin, Guasmin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
The calculation results obtained by using multiple linear regression model analysis shows that the asset structure and company size simultaneously or simultaneously have a positive and significant effect on the capital structure. This is supported by the F-count value of 24,957 at a significance level of 0.000 which is smaller than 0.05, which means that the F-count value is greater than the F-table value, which is 24.957 > 3.134. Asset structure partially has a negative and significant effect on capital structure. This is supported by the t-count value of -4.813 at a significance level of 0.000 which is smaller than 0.05 which means that the t-count value is smaller than the t-table value, namely -4.813 <1.994. Firm size partially positive and significant effect on capital structure. This is supported by the t-count value of 4.922 at a significance level of 0.000 which is smaller than 0.05, which means that the t-count value is greater than the t-table value, namely 4.922 > 1.994.